Flying to the Cloud : Governments Seek Gains from Cloud Computing - Melhem, Samia; Kim, Seunghyun (World Bank, Washington, DC, 2017)
The transition to cloud computing broadly means shifting programs and data from personal or office hardware to shared hardware that many individuals and organizations access over the Internet. That migration is happening fast. By 2019, according to the information technology company Cisco, 83 percent of all global data center traffic will come from cloud services. And the profitability of the cloud services unit of Amazon, the leader in the worldwide cloud computing market, has been growing strongly. Relative to conventional computing, the cloud can offer more efficiency, scalability, and flexible real-time service to employees, customers, and citizens. Cloud computing, a fast-growing business, appeals to governments that want to provide more accessible, secure, and cost-effective public services. However, putting government data in the cloud—that is, on remote, Internet-connected devices owned by another, typically private, organization—poses the question of readiness to handle issues that are inherent in the technology, including security, dependability, and the scope of control that might be exercised by the owner of the cloud hardware and the Internet service provider. The World Bank’s Information and Communication Technologies (ICT) unit in collaboration with Accenture Consulting, recently developed a toolkit that can assess government readiness for cloud migration. It is conducting pilot studies to improve and refine the ability of the toolkit to provide recommendations to interested national policy makers and digital leaders.